Optimization of Fused Deposition Modeling (FDM) Machine Parameters for Carbon Fiber Tensile Strength Using the Taguchi Method - Prayoga, Adimas Dwi; Mukti, Abdi Satryo; Mahameru, Rolland Darin Khalifah; Rosyadi, Willdan; lestari, Wahyu Dwi (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2024)
3D printing using Fused Deposition Modeling (FDM) technology has emerged as a promising approach for manufacturing components with composite materials such as carbon fiber. This study aims to optimize the parameters of FDM machines for carbon fiber tensile strength using the Taguchi Method. The optimized FDM machine parameters include nozzle temperature, infill density, printing speed, layer thickness, infill pattern, and orientation. Experiments were conducted based on the Taguchi experimental design with an L27 Orthogonal Array (3^6) matrix, resulting in 27 experiments with different parameter combinations. After printing was completed, tensile tests were performed to measure the tensile strength of the printed samples. The results of the analysis using the Taguchi Method show the optimal settings of the FDM machine parameters to achieve maximum tensile strength for carbon fiber material. The analysis results show that the parameters that can optimize the tensile test response are nozzle temperature at level 2 (230°C), infill density at level 3 (80%), printing speed at level 3 (100 mm/s), layer thickness at level 3 (0.3 mm), infill pattern at level 1 (line), and orientation at level 3 (30°) with the highest tensile test value of 27.7766 MPa. This study provides an important contribution to the development of 3D printing techniques with carbon fiber, by identifying the optimal settings that can improve the mechanical performance of printed components. It is expected that the results of this study can be used as a practical guideline for the 3D printing industry in optimizing FDM machine parameters for printing carbon fiber-based composite materials.